Making Up Your Mind: Perceptual Retraining with Mirror to Increase Self-Acceptance for Negative Body Image in Generation Z Teens - Rina Rifayanti; Elis Darmayasary Bachtiar; Khairun Nisa; Fasya Rizkyta Anwar (Universitas Pendidikan Ganesha, 2023)
In this study focused on negative body image because, every individual who has a negative body image then he will be difficult to accept or love himself that will make them experience a lot of problems with his body, for example feeling dissatisfied with the body owned, eating disorders, doing a diet that is too strict, depression, and others. The goal of the study was to analyze the increase in self-acceptance of negative body image in generation Z adolescents by using perceptual retraining with mirrors. This type of research is experimental research with a quantitative approach. The sample number of studies was 30 students who were divided into two groups. The research instruments used there are self-acceptance and body image scales. The data analysis method used in this study is statistical analysis is Paired T-test samples. The results showed a value of P = 0.000 (P <0.050) and resulted in a value of P = 0.000 (P <0.000) in the body image of the experimental group. While in the results of self-acceptance the control group using the sample paired t-test resulted in a value of P = 0.000 (P < 0.050) and produced a value of P = 0.000 (P < 0.000) of the body image scale of the control group. This suggests that subjects using perceptual retraining with mirror experienced increased self-acceptance of negative body image. The implication of this study is that mirrored perceptual retraining methods can be used as interventions to help generation Z adolescents overcome negative body image and improve their self-confidence and mental health.